2023
DOI: 10.21608/ejmm.2023.277785
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Infection by Carbapenem-Resistant Acinetobacter Species in ICUs in Assiut, Egypt

Abstract: The genus Acinetobacter is one of the main fears of hospital-acquired infection (HAI) wide-reaching mostly in ICUs. Objectives: This study aimed to identify the incidence of carbapenem-resistant Acinetobacter (CRA) HAI in Assiut University Hospitals ICU and determine their antimicrobial susceptibility profile. Methodology:The study included 1204 clinical samples from 928 patients with HAI and 625 environmental samples. Carbapenemase production was detected phenotypically by MIC determination using imipenem, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…exhibited a higher resistance rate against levofloxacin (83.3%), along with resistance rates ranging from 61.2% to 72.3% for all tested cephalosporins, carbapenems, and aminoglycosides, while the resistance rate for TMP-SMX was 55.6%. In a different study, it was observed that 100% of the test isolates were resistant to piperacillin, ceftazidime, cefepime, and aztreonam, with a 94.5% resistance rate to ciprofloxacin that is consistent with our study 20 . The high level of antibiotic resistance observed in our study could be linked to the selective pressure exerted by the frequent use of these drugs in our hospitals, as well as the ability of Acinetobacter to rapidly acquire resistance genes through horizontal gene transfer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…exhibited a higher resistance rate against levofloxacin (83.3%), along with resistance rates ranging from 61.2% to 72.3% for all tested cephalosporins, carbapenems, and aminoglycosides, while the resistance rate for TMP-SMX was 55.6%. In a different study, it was observed that 100% of the test isolates were resistant to piperacillin, ceftazidime, cefepime, and aztreonam, with a 94.5% resistance rate to ciprofloxacin that is consistent with our study 20 . The high level of antibiotic resistance observed in our study could be linked to the selective pressure exerted by the frequent use of these drugs in our hospitals, as well as the ability of Acinetobacter to rapidly acquire resistance genes through horizontal gene transfer.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence rate of XDR and MDR isolates in our study was 82% and 16%, respectively. Similarly, a study from Egypt noticed that 91.7% of isolates were XDR and 8.3% of them were MDR 20 . Another study conducted by Khalifa et al 27 revealed that 50% of Acinetobacter isolates were XDR and 16.6% were MDR.…”
Section: Discussionmentioning
confidence: 89%